MODERN PROBLEMS OF CHEMISTRY METHODOLOGY (1950-2000) (Spectrum Journal of Innovation, Reforms and Development, 2022)
Since 1917, throughout the twentieth century, general secondary education has been undergoing gradual reform. The need for reforms was due to changing socio-social and ideological factors, which at the first stage included the need to provide students with a certain amount of knowledge, skills and abilities laid down in the subject systematic courses and constituting the foundations of sciences.